Proposition of the relational boycott. (16th November 2015) - Cruz, Breno de Paula Andrade; Botelho, Delane
Abstract : Purpose: – The purpose of this study is to identify, in the context of virtual social networks (VSNs), other types of boycott which have not yet been addressed in the literature. We relate the boycott(s) emerged on the VSNs with those found in the literature (economic, religious, of minorities, ecological and labor boycott), and verify the motivation that must be unique to such context. Design/methodology/approach: – Grounded theory was used in triangulation with netnography (interacting with 183 customers), non-participant observation (68 postings/47 complaints, from 2009 to 2012) and in-depth interview (15 consumers). Findings: – A new classification of boycott was proposed, which emerged on the basis of company service quality, named "relational boycott", which can generate additional acts of repudiation, such as interaction, unity of the group and encouragement of third parties. Research limitations/implications: – The model of relational boycott proposed was not empirically tested, but insights for future test are provided. Practical implications: – A model of how the relational boycott is structured is provided, being a deliberate, primary act of the consumer resulting from the management problems of a company generating backlash actions. Social implications: – Since boycott represents a mechanism of protesting, it is a way that consumers pressure companies to provide better services and products, which may improve consumer's wellbeing in the long range. Originality/value: – A new type of boycott emerges in the research, named relational boycott, structured in a model that can be tested empirically.